Strength & conditioning of a world class female squash player - a case study - Gallagher, C. (Journal of Australian Strength and Conditioning, 2018)
Research into the physical characteristics of squash and female athletes in particular is greatly lacking, this research provides insights into the strength & conditioning (S&C) capabilities of a world class female squash player.